Banking distortions in the financial structures of post-war economies : the experience of Jamaica, Korea, Trinidad and Tobago and the USA. - Clarke, Laurence C. ([s.n.] KingstonJM, 1986)
Assesses evolution of the banking system in the financial structures of selected developed and developing countries' economies in the post war years 1960 to 1980. Discusses elements and dynamics of finance and banking processes. Identifies and discusses emergence of a phenomenon called `financial asphyxiation' (FA) which is said to exist when the banking subsector commands a larger share of the financial system despite less efficient performances than non-banks. Formulates a theory of `FA' and identifies its presence in four economies. Discusses the determinate factors of the phenomenon and its distortive impact on the economy. Discusses costs of `financial asphyxiation'and corrective policies of LDC's. Recommends reforms.